(untitled) (Research, Society and Development, 2023)
Drug-induced liver injury (DILI) is a liver injury caused by medicines, herbs and xenobiotics, which lead to liver changes. The incidence of DILI in pediatrics is unknown, as cases are subclinical or underreported. The objective was to carry out a systematic review of the literature to determine the main drugs involved in DILI in pediatrics. 339 articles were identified in the databases, 48 of which were selected for full reading and after selection and eligibility, a total of 13 articles were obtained. DILI in pediatrics is a challenge due to its vast clinic, difficult diagnosis and non-specific treatment. A high and heterogeneous possibility of drugs that cause liver damage in children was verified. It is important that studies are carried out to ensure better results regarding diagnosis, prevention and treatment, as well as the organization of databases with information on adverse liver events involving the use of drugs in pediatrics.